Climate Change and Natural Hazard Risk Assessment Framework for Coastal Cable-Stayed Bridges - Markogiannaki, Olga (Frontiers in Built Environment, 2019)
Cable-stayed bridges have been used widely in the last 60 years in bridge construction practice and are key components of transportation networks. Therefore, the potential damages and losses, either in terms of economic cost or fatalities due to natural or man-made threats could become considerably large. Several researchers have identified the significance of risk assessment, especially to natural hazards and have proposed risk assessment frameworks for bridges. Recently, it has been identified that climate change affects the occurrence of extreme events and should be also incorporated in risk assessment. In the present research work, a risk assessment framework for cable-stayed bridges is proposed. The goal is to prioritize single and total risk to provide a useful tool in the decision-making process on the design and maintenance actions for cable-stayed bridges. Herein, the case study is an indicative design alternative of a cable-stayed bridge in a coastal area in the New York Region. which is expected to face sea-level rise due to climate change. Multi-hazard risk evaluation on the investigated bridge shows that it has low risk to the seismic hazard, while it has increased risk to hurricanes, which changes from low to high depending on the investigated sea-level rise projections and hurricane intensity levels. Hence, hurricane governs the resulting total risk of the case study bridge.